1985
DOI: 10.3354/meps022199
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behavior of euryhaline phytoplankton communities to arsenic stress

Abstract: Long-term experiments performed with large-volume continuous cultures of natural phytoplankton assemblages exposed to low levels of arsenate (1 to 10 X ambient concentrations) have shown that arsenate is differentially inhibiting to some phytoplankton species. This observed variance in sensitivity is sufficient to cause a marked change in species composition and succession of dominant species in arsenic-treated assemblages with a potential for impact upon carbon transfer between trophic levels, even though est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Aquifers in La Pampa province have been reported to contain high concentrations of arsenic (up to 5300 mg/l), mainly as a consequence of the evaporation under semiarid climatic conditions (Smedley et al, 2002). As arsenic stress can induce shifts in diatom species dominance (Sanders and Cibik, 1985), arsenic concentration might be one of the ''overlooked'' factors responsible for the unexplained variance in CCA. Nevertheless, the explained percentage is considerably greater than those found in many other similar biological datasets, which have a large number of samples with many zero values, and have been used to develop transfer functions (Gasse et al , 1997;Jones and Juggins, 1995).…”
Section: Diatomsmentioning
confidence: 99%
“…Aquifers in La Pampa province have been reported to contain high concentrations of arsenic (up to 5300 mg/l), mainly as a consequence of the evaporation under semiarid climatic conditions (Smedley et al, 2002). As arsenic stress can induce shifts in diatom species dominance (Sanders and Cibik, 1985), arsenic concentration might be one of the ''overlooked'' factors responsible for the unexplained variance in CCA. Nevertheless, the explained percentage is considerably greater than those found in many other similar biological datasets, which have a large number of samples with many zero values, and have been used to develop transfer functions (Gasse et al , 1997;Jones and Juggins, 1995).…”
Section: Diatomsmentioning
confidence: 99%
“…Nevertheless, microorganisms do not accumulate As to an unlimited extent. Several studies observed toxicity effects, already at this level of the food chain [9,10]. In the scope of biomagnification, it would be logical that the accumulation of As versus its level in water would be even more pronounced higher up the food chain.…”
Section: Origin and Chemical Forms Of As In Fish And Shellfishmentioning
confidence: 99%
“…Nutrient enrichment can increase algal growth (including harmful algal blooms), decrease light penetration, cause accumulation of organic carbon in the benthos, and consequent hypoxia or anoxia in bottom waters (Schelske and Stoermer 1971;Turpin and Harrison 1979;Oviatt et al 1989;Riegman 1995). Trace element enrichment suppresses primary production, alters the species composition and size of the phytoplankton community (Sanders and Cibik 1985;Brand et al 1986;Sanders et al 1994), and increases accumulation of trace elements in the sediment and the food chain (Goldberg et al 1978;Han and Hung 1990).…”
Section: Introductionmentioning
confidence: 99%